Obstacle avoidance using buffered voronoi cells based on local information from a laser range scanner. (17th January 2023) - Motonaka, Kimiko; Miyoshi, Seiji
Abstract : In this study, we present an approach for implementing an autonomous navigation method, including obstacle avoidance, based on buffered Voronoi cells (BVCs) in a quadrotor. The navigation method using BVC is suitable for online processing because it can determine the control input from only the approximate relative distance between the current position and the obstacles without complex information, such as velocity or accurate obstacle positions. The method has been confirmed to work well through simulations and experiments in previous studies. These experiments assumed that quadrotors could obtain the relative positions of nearby objects using mutual communication with other quadrotors. However, in practical use, there are cases in which quadrotors should move based on the local information gathered by the mounted sensors. Therefore, we propose a method for obtaining the necessary information to calculate the area of the BVC from a laser range scanner mounted on the quadrotor to enable the quadrotor to reach a specified target position without colliding with obstacles. In addition, we propose a simple method for handling deadlocks that can occur depending on the position of the obstacles. GRAPHICAL ABSTRACT: UF0001